Antioxidant Activity of Syzygium oleana - Anggraini, Tuty (Pakistan Journal of Nutrition, 2017)
Background and Objectives: Syzygium oleana (S. oleana) is a plant that can potentially serve as a natural food colorant. Anthocyanin present in fruit and red (young) leaves also functions as an antioxidant. The purpose of this study was to obtain information about the antioxidant activity of S. oleana and to measure the total polyphenol and anthocyanin content in its fruits and red leaves using 3 kinds of solvents: Water, methanol and ethanol. Materials and Methods: This study used the exploratory method. The total phenolic content of the S. oleana fruit and leaf extract was measured using gallic acid as a standard. The DPPH was used to measure the antioxidant activities of S. oleana fruit and leaf extracts. Anthocyanin pigment concentration was calculated. Results: The results showed that the antioxidant content is activated up to 3.87, 26.4 and 65.65% with water, methanol and ethanol solvents, respectively. The total polyphenol content in water, methanol and ethanol are 55.37, 78.87 and 122.10 mg mL–1, respectively. Anthocyanin content measured in water, methanol and ethanol are 16.42, 19.20 and 15.16%, respectively. Conclusion: This study suggests that S. oleana can be applied as a food colorant and that the best solvent for extraction is methanol.